Forensic document examination in the 21st century - Seaman Kelly, Jan; Angel, Miriam (Boca Raton : CRC Press, 2021)
"Forensic Document Examination in the 21st Century covers the latest technology and techniques providing a complete resource on contemporary issues and methods in forensic document examination. Forensic document examiners provide their findings as expert testimony in court. Due to rapid changes in technology, including digital documents, printing and photocopying capabilities, and more, there is a great need for this up-to-date reference. The examination of documents can include comparison of handwriting or hand-printing; detection of alterations or photocopier and computer manipulation; restoration or decipherment of erased and obliterated writing; visualization of latent impressions; the identification of printing processes; and differentiation of inks. Computer-generated documents are prevalent, and electronically-captured signatures are becoming more widespread, meaning the knowledge of advances in technology and adoption of new validated techniques and methods of document examination are crucial to the reliability of forensic opinions. Forensic Document Examination in the 21st Century includes the latest research on the subject and with contributions from leading experts on their various areas of expertise. The book will be a welcome addition to the literature and support the foundational basis for methods and procedures for use it expert testimony in court, serving as a resource for forensic document examiners, trainees, and those in the criminal and legal communities who use the services of expert document examiners and witnesses"--
OCLC-licensed vendor bibliographic record.
Keywords: Forensic sciences -- History -- 21st century; Criminal investigation -- History -- 21st century; LAW / Criminal Law / General